The statements are given as follows:

P ∨ (~P & Q & R)

(~P & Q) ∨ (P & ~Q) & S

Conjunctive normal form implies that all terms in the equation must have the "&" symbol between them. In the two sentences given above, we can see we have the "∨" symbol between the terms. Let us convert each of them into conjunctive normal form one-by-one.

**Statement 1: P ∨ (~P & Q & R)**

P ∨ (~P & Q & R)

= (P ∨ ~P) & (P ∨ Q) & (P ∨ R)

= (P ∨ Q) & (P ∨ R)

We used two properties here:

While opening the brackets, whatever is outside the bracket must be multiplied/operated with each term inside the bracket.

(P ∨ ~P) = NULL, as it is always TRUE.

**Statement 2: (~P & Q) ∨ (P & ~Q) & S**

(~P & Q) ∨ (P & ~Q) & S

= ((~P ∨ (P & ~Q)) & (Q ∨ (P & ~Q))) & S

= ((~P ∨ P) & (~P ∨~Q)) & ((Q ∨ P) & (Q ∨~Q)) & S

= (~P ∨~Q) & (Q ∨ P) & S

We have converted both statements into Conjunctive Normal Form.

## コメント